Preparation method and application of composite cathode hydrogen evolution catalyst

By preparing a two-dimensional transition metal-nitrogen-carbon composite catalyst with uniformly supported ruthenium clusters, the problems of limited water dissociation rate and stability of Ru-based catalysts under high current density were solved, achieving low-cost, high-activity and stable alkaline HER performance.

CN119592991APending Publication Date: 2025-03-11NANJING DAQUAN ZHONGKE HYDROGEN ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411911676.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing Ru-based catalysts have limited water dissociation rates at high current densities, and sub-nano clusters are prone to migration and aggregation at high current densities and high temperatures, leading to decreased activity and making it difficult to meet the actual needs of AEMWE.

Method used

A metal-organic precursor-zeolite imidazole framework was prepared by mixing zinc nitrate, 2-methylimidazole and transition metal salts. After high-temperature melting pyrolysis and acid washing, combined with the stirring and high-temperature heat treatment of ruthenium source and two-dimensional transition metal-nitrogen-carbon single-atom support material, a two-dimensional transition metal-nitrogen-carbon composite catalyst with uniformly loaded ruthenium clusters was prepared.

Benefits of technology

It improves the water dissociation kinetics and stability of ruthenium clusters in alkaline HER processes, reduces the amount of precious metals used, has low cost and excellent HER activity and stability, and is suitable for anion exchange membrane electrolysis of water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592991A_ABST
    Figure CN119592991A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a composite cathode hydrogen evolution catalyst. The preparation method comprises the following steps: mixing zinc nitrate, 2-methylimidazole, methanol and different transition metal salts, carrying out ultrasonic standing for 24 hours, carrying out alcohol washing, carrying out centrifugal separation, and drying in a drying oven to obtain a metal organic precursor-zeolite imidazole skeleton (M-ZIF-8); the preparation method comprises the following steps: uniformly mixing M-ZIF-8 with a salt template, carrying out high-temperature melting pyrolysis in an inert atmosphere, carrying out acid pickling, deionized water washing and centrifugal separation on the obtained product, and freeze-drying to prepare a two-dimensional transition metal-nitrogen-carbon monatomic carrier material (M-N-C); the preparation method comprises the following steps: stirring and adsorbing a ruthenium source and M-N-C in an aqueous solution, freezing and drying the uniformly mixed solution, and performing high-temperature heat treatment in a hydrogen-argon mixed atmosphere to obtain the ruthenium cluster uniformly loaded two-dimensional transition metal-nitrogen-carbon composite catalyst material. According to the catalyst prepared by the method, the dosage of noble metal is reduced, the cost of the catalyst is reduced, and the catalyst has excellent HER activity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material synthesis and electrocatalysis, and specifically relates to a preparation method and application of a composite cathode hydrogen evolution catalyst. Background Art

[0002] Hydrogen, as an important clean energy carrier and widely used industrial raw material, plays a very important role in promoting energy transformation and industrial decarbonization, and is also an important medium to support the large-scale development of renewable energy. Therefore, vigorously developing renewable energy-coupled water electrolysis technology to produce green hydrogen and increasing the proportion of green hydrogen in the hydrogen energy supply are important ways to achieve green energy transformation and my country's "dual carbon" goals. Anion exchange membrane water electrolysis (AEMWE) and proton exchange membrane water electrolysis (PEMWE) technologies, with their rapid response, compact stack design and high efficiency, have become key technologies for achieving efficient and large-scale green hydrogen production, and are expected to promote the transformation of the global energy structure and the green and low-carbon process. Compared with the high reliance on precious metals (such as Pt and IrO x ), AEMWE technology can use the same low-cost non-precious metal catalysts as traditional alkaline (ALK) water electrolysis technology, making it more competitive in future industrial applications. As an important component of AEMWE water decomposition to produce hydrogen, the hydrogen evolution reaction (HER) is crucial to the development of green energy technology. The precious metal Pt is still considered to be the most effective HER catalyst because of its optimal hydrogen adsorption Gibbs free energy (ΔG*H). However, traditional Pt / C catalysts face challenges such as high cost and slow water dissociation kinetics under alkaline conditions, which restricts the large-scale application of Pt catalysts in the AEMWE field. Therefore, the development of low-cost and highly catalytically active non-Pt hydrogen evolution electrocatalysts is crucial to building an efficient and practical hydrogen energy system.

[0003] Recently, ruthenium (Ru) has been widely used due to its similar hydrogen adsorption Gibbs free energy (ΔG) to that of Pt. *H) and the price is only 1 / 2 of Pt, which has attracted widespread attention from researchers. In particular, sub-nano clusters (<2nm) with a size between single atoms (SAs) and nanoparticles (NPs) are considered to be an ideal choice to replace the precious metal Pt due to their unique electronic structure configuration and relatively low cost, as well as their high catalytic activity and excellent stability in the three-electrode system. However, there are huge challenges in the application of Ru-based catalysts under membrane electrolysis conditions, mainly in the following aspects: 1) At high current density, the water dissociation rate of Ru-based catalysts is still subject to certain restrictions, which makes it difficult to meet actual needs. 2) Since the cohesive energy of Ru is much greater than that of Pt, when the particle size is reduced to sub-nano clusters, these clusters show obvious thermodynamic instability and are more likely to agglomerate than Pt. Especially during the membrane electrode test at high current density and high temperature, the migration, aggregation and Ostwald ripening process of particles will cause the surface energy to rise sharply, prompting Ru clusters to tend to form larger crystal structures, which in turn leads to a decrease in activity. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0006] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a composite cathode hydrogen evolution catalyst.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising: Zinc nitrate, 2-methylimidazole, methanol and different transition metal salts were mixed and ultrasonically placed for 24 hours, and then washed with alcohol, centrifuged and dried in an oven to prepare a metal organic precursor-zeolite imidazole framework; The metal organic precursor-zeolite imidazole framework and the salt template are uniformly mixed, melted and pyrolyzed at high temperature under an inert atmosphere, and the obtained product is acid-washed, washed with deionized water, centrifuged and freeze-dried to prepare a two-dimensional transition metal-nitrogen-carbon single atom carrier material; The ruthenium source and the two-dimensional transition metal-nitrogen-carbon single atom carrier material are stirred and adsorbed in an aqueous solution, the evenly mixed solution is frozen and dried, and then subjected to high-temperature heat treatment in a hydrogen-argon mixed atmosphere to obtain a two-dimensional transition metal-nitrogen-carbon composite catalyst material uniformly loaded with ruthenium clusters.

[0008] As a preferred embodiment of the method for preparing the composite cathode hydrogen evolution catalyst of the present invention, the transition metal salt comprises nitrates and acetylacetonate of iron, cobalt, nickel and copper.

[0009] As a preferred embodiment of the method for preparing the composite cathode hydrogen evolution catalyst of the present invention, the mass ratio of the zinc nitrate to 2-methylimidazole is 1:(2-4).

[0010] As a preferred embodiment of the method for preparing the composite cathode hydrogen evolution catalyst of the present invention, the molar ratio of the transition metal salt to zinc nitrate is (0.1-0.3):1.

[0011] As a preferred embodiment of the method for preparing the composite cathode hydrogen evolution catalyst of the present invention, the mass ratio of the metal organic precursor - zeolite imidazole framework to the salt template is 1: (10-30).

[0012] As a preferred embodiment of the method for preparing the composite cathode hydrogen evolution catalyst of the present invention, the pyrolysis temperature is 800-1000° C., the heating rate is 2-5° C. / min, the time is 1-3 hours, and the inert atmosphere is nitrogen or argon.

[0013] As a preferred embodiment of the method for preparing the composite cathode hydrogen evolution catalyst of the present invention, the mass ratio of ruthenium to the two-dimensional transition metal-nitrogen-carbon single atom carrier material is (0.01-0.05):1.

[0014] As a preferred embodiment of the method for preparing the composite cathode hydrogen evolution catalyst of the present invention, the stirring temperature is 25-45° C. and the stirring time is 6-12 h.

[0015] As a preferred embodiment of the method for preparing the composite cathode hydrogen evolution catalyst of the present invention, the high temperature pyrolysis temperature under the hydrogen-argon mixed atmosphere is 500-700°C, the heating rate is 2-5°C / min, and the time is 1-3h.

[0016] As a preferred solution for the application of the composite cathode hydrogen evolution catalyst of the present invention, the prepared ruthenium clusters are uniformly loaded with a two-dimensional transition metal-nitrogen-carbon composite catalyst as an alkaline hydrogen evolution reaction catalyst and applied to anion exchange membrane water electrolysis.

[0017] Beneficial effects of the present invention: The present invention provides a preparation method and application of a composite cathode hydrogen evolution catalyst, and obtains a two-dimensional transition metal-nitrogen-carbon single atom carrier uniformly loaded with ruthenium clusters. Compared with traditional carbon materials as carriers, ruthenium clusters loaded on MNC single atom carriers prepared by salt template assisted pyrolysis can better improve the water dissociation kinetics and stability of ruthenium clusters in the alkaline HER process. The catalyst prepared by this method not only reduces the amount of precious metals used and reduces the cost of the catalyst, but also has excellent HER activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them: Figure 1 This is the spherical aberration electron microscopy (AC-STEM) image of the two-dimensional transitional cobalt metal-nitrogen-carbon single atom support obtained by salt template-assisted high-temperature pyrolysis of M-ZIF-8 organic precursor.

[0019] Figure 2 This is an AC-STEM image of a two-dimensional transition cobalt metal-nitrogen-carbon single atom carrier uniformly loaded with a ruthenium cluster composite catalyst prepared in Example 1 of the present invention.

[0020] Figure 3 The two-dimensional transition cobalt metal-nitrogen-carbon single atom carrier prepared in Examples 1-4 of the present invention is loaded with ruthenium clusters (m Ru :m CoNC =(0.02~0.05): 1) Comparison of the electrochemical hydrogen evolution polarization curves (LSV) of the composite catalyst and the commercial Pt / C, Ru / C and Ru / NC catalysts in control examples 1-3 in 1M KOH solution.

[0021] Figure 4 The two-dimensional transition cobalt metal-nitrogen-carbon single atom carrier prepared in Example 1 of the present invention is loaded with ruthenium clusters (m Ru :m CoNC =1:30) comparison of the electrochemical stability of the composite catalyst and the Ru / NC catalyst in Control Example 3 in 1M KOH solution.

[0022] Figure 5 The two-dimensional transition cobalt metal-nitrogen-carbon single atom carrier uniformly loaded with ruthenium cluster composite catalyst (m Ru :m CoNC=1:30) as cathode catalyst for AEMWE water electrolysis device performance comparison chart. DETAILED DESCRIPTION

[0023] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0024] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0025] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments. Example

[0026] This embodiment provides a preparation method and application of a composite cathode hydrogen evolution catalyst, specifically: Preparation of ruthenium clusters uniformly loaded with two-dimensional transition cobalt metal-nitrogen-carbon composite catalyst materials: Weigh 1000 mg zinc nitrate, 35.6 mg cobalt acetylacetonate, and 2000 mg 2-methylimidazole and dissolve them in 30 mL methanol. Mix and ultrasonicate, and let stand for 24 hours. Then, centrifuge the obtained precipitate, wash it with anhydrous ethanol several times, and place it in an oven at 40-70°C and dry it for 6-12 hours to obtain Co-ZIF-8 metal organic precursor. Weigh 200 mg of Co-ZIF-8 metal organic precursor and 4000 mg of solid potassium chloride (KCl) and mix and grind them in a mortar, pyrolyze them at high temperature under an argon atmosphere, the pyrolysis temperature is 800-1000°C, the heating rate is 2-5°C / min, the insulation time is 1-3h, after cooling to room temperature, soak in dilute hydrochloric acid for 5-10h, centrifuge, wash with deionized water for several times until the pH is neutral, and obtain a Co-NC single atom catalyst carrier; 40 mg of the obtained Co-NC single-atom carrier material was ultrasonically dispersed in 40 mL of deionized water. Subsequently, 500 μL of ruthenium chloride aqueous solution (mass concentration of 15 mg / mL, mass fraction of ruthenium chloride of 37%) was added dropwise to the Co-NC single-atom material dispersion (the mass ratio of metal ruthenium to transition metal-nitrogen-carbon was controlled). Ru :m CoNC=1:30), stirred for 12 hours, and then the mixed solution was freeze-dried. After freeze-drying, the obtained solid powder was placed in a porcelain boat and pyrolyzed at high temperature in a hydrogen-argon mixed atmosphere. The pyrolysis temperature was 500°C, and the temperature was kept at 500°C for 2 hours. The heating rate was 3°C / min, and the ruthenium clusters were uniformly loaded with a two-dimensional transition metal-nitrogen-carbon composite catalyst material (m Ru :m CoNC =1:30) catalyst material.

[0027] From the spherical aberration electron microscopy image of the sample ( Figure 1 ) It can be seen that the prepared Co-NC support is a single-atom material.

[0028] Spherical aberration electron microscopy image of a ruthenium cluster composite catalyst uniformly loaded on a two-dimensional transitional cobalt metal-nitrogen-carbon single atom support ( Figure 2 ) It can be seen that the Ru clusters with a size of <2 nm are uniformly distributed on the Co-NC single atom substrate.

[0029] The alkaline HER performance test method of the above-prepared two-dimensional transition cobalt metal-nitrogen-carbon single atom uniformly loaded ruthenium cluster composite catalyst in a three-electrode system is as follows: 2 mg of the catalyst prepared above was weighed and dispersed in a mixed solution of 190 μL of deionized water and 300 μL of isopropanol, and then 10 μL of Nafion solution (mass fraction 5%) was added and ultrasonically treated for 30 min to form a uniform slurry (ink); 10 μL of catalyst ink was dispersed on a glassy carbon electrode with a diameter of 5 mm. After being dried naturally, it was used as the working electrode. The mercury / mercury oxide electrode and graphite carbon rod were used as the reference electrode and the counter electrode respectively. The HER performance of the prepared catalysts was tested in 1M KOH solution using an electrochemical workstation (CHI660e) and a rotating disk electrode (RDE) in a standard three-electrode system.

[0030] Test method: Electrochemical polarization curve (LSV) test was performed in the voltage range of -0.6~0.1Vvs.RHE, with a scan rate of 0.01V·s -1 , the rotation speed is 1600rpm. All potentials in LSV are corrected with ir compensation. The stability test is obtained by testing the it curve at -0.125VvsRHE.

[0031] Preparation and testing method of the above-prepared two-dimensional transition cobalt metal-nitrogen-carbon single atom uniformly loaded ruthenium cluster composite catalyst on the AEM membrane electrode: The two-dimensional transition cobalt metal-nitrogen-carbon single atom carrier obtained in Example 1 is uniformly loaded with a ruthenium cluster composite catalyst (m Ru :mCoNC =1:30) was prepared into catalyst slurry (ink), and the catalyst was sprayed on carbon fiber paper as cathode catalyst using ultrasonic spraying equipment. The cathode catalyst loading was (2 mg / cm 2 ), the anode used was homemade NiFe-LDH grown on nickel foam, and the anion exchange membrane was a purchased commercial anion exchange membrane, which were assembled into an AEMWE water electrolysis device for water electrolysis performance testing.

[0032] At 60℃, the current density reaches 2A / cm 2 When the potential is only 1.81V, the current density reaches 2A / cm at 80℃. 2 When the potential is only 1.75 V, its performance is better than that of the AEMWE water electrolysis device assembled with the same commercial Pt / C as the cathode (see Figure 5 ). Therefore, this material shows great industrial application value as a cathode HER catalyst for AEMWE water electrolysis. Example

[0033] Preparation of two-dimensional transition cobalt metal-nitrogen-carbon single atom carrier uniformly loaded with ruthenium cluster composite catalyst materials: Weigh 1000 mg zinc nitrate, 35.6 mg cobalt acetylacetonate, and 2000 mg 2-methylimidazole and dissolve them in 30 mL methanol. Mix and ultrasonicate, and let stand for 24 hours. Then, centrifuge the obtained precipitate, wash it with anhydrous ethanol several times, and place it in an oven at 40-70°C and dry it for 6-12 hours to obtain Co-ZIF-8 metal organic precursor. Weigh 200 mg of Co-ZIF-8 metal organic precursor and 4000 mg of solid potassium chloride (KCl) and mix and grind them in a mortar, pyrolyze them at high temperature under an argon atmosphere, the pyrolysis temperature is 800-1000°C, the heating rate is 2-5°C / min, the insulation time is 1-3h, after cooling to room temperature, soak in dilute hydrochloric acid for 5-10h, centrifuge, wash with deionized water for several times until the pH is neutral, and obtain a Co-NC single atom catalyst carrier; 40 mg of the obtained Co-NC single-atom carrier material was ultrasonically dispersed in 40 mL of deionized water. Subsequently, 750 μL of ruthenium chloride aqueous solution (mass concentration of 15 mg / mL) was added dropwise to the Co-NC single-atom material dispersion (the mass ratio of metal ruthenium to transition metal-nitrogen-carbon was controlled). Ru :m CoNC=1:20), stirred for 12 hours, and then the mixed solution was freeze-dried. After freeze-drying, the obtained solid powder was placed in a porcelain boat and pyrolyzed at high temperature in a hydrogen-argon mixed atmosphere. The pyrolysis temperature was 500°C, and the temperature was kept at 500°C for 2 hours. The heating rate was 3°C / min, and the ruthenium clusters were uniformly loaded with a two-dimensional transition metal-nitrogen-carbon composite catalyst material (m Ru :m CoNC =1:20) catalyst material.

[0034] The ruthenium clusters prepared above are uniformly loaded with a two-dimensional transition metal-nitrogen-carbon composite catalyst material (m Ru :m CoNC =1:20) was tested in the same way as in Example 1. The HER activity was shown in Figure 3 . Example

[0035] Preparation of ruthenium cluster composite catalyst material uniformly loaded on two-dimensional transition cobalt metal-nitrogen-carbon single atom carrier: Weigh 1000 mg zinc nitrate, 35.6 mg cobalt acetylacetonate, and 2000 mg 2-methylimidazole and dissolve them in 30 mL methanol. Mix and ultrasonicate, and let stand for 24 hours. Then, centrifuge the obtained precipitate, wash it with anhydrous ethanol several times, and place it in an oven at 40-70°C and dry it for 6-12 hours to obtain Co-ZIF-8 metal organic precursor. Weigh 200 mg of Co-ZIF-8 metal organic precursor and 4000 mg of solid potassium chloride (KCl) and mix and grind them in a mortar, pyrolyze them at high temperature under an argon atmosphere, the pyrolysis temperature is 800-1000°C, the heating rate is 2-5°C / min, the insulation time is 1-3h, after cooling to room temperature, soak in dilute hydrochloric acid for 5-10h, centrifuge, wash with deionized water for several times until the pH is neutral, and obtain a Co-NC single atom catalyst carrier; 40 mg of the obtained Co-NC single-atom carrier material was ultrasonically dispersed in 40 mL of deionized water. Subsequently, 400 μL of ruthenium chloride aqueous solution (mass concentration of 15 mg / mL) was added dropwise to the Co-NC single-atom material dispersion (the mass ratio of metal ruthenium to transition metal-nitrogen-carbon was controlled). Ru :m CoNC =1:40), stirred for 12 hours, and then the mixed solution was freeze-dried. After freeze-drying, the obtained solid powder was placed in a porcelain boat and pyrolyzed at high temperature in a hydrogen-argon mixed atmosphere. The pyrolysis temperature was 500°C, and the temperature was kept at 500°C for 2 hours. The heating rate was 3°C / min, and the ruthenium clusters were uniformly loaded with a two-dimensional transition metal-nitrogen-carbon composite catalyst material (m Ru :m CoNC =1:40) catalyst material.

[0036] The ruthenium clusters prepared above are uniformly loaded with a two-dimensional transition metal-nitrogen-carbon composite catalyst material (m Ru :m CoNC =1:40) was tested in the same way as in Example 1. The HER activity was shown in Figure 3 . Example

[0037] Preparation of ruthenium cluster composite catalyst material uniformly loaded on two-dimensional transition cobalt metal-nitrogen-carbon single atom carrier: Weigh 1000 mg zinc nitrate, 35.6 mg cobalt acetylacetonate, and 2000 mg 2-methylimidazole and dissolve them in 30 mL methanol. Mix and ultrasonicate, and let stand for 24 hours. Then, centrifuge the obtained precipitate, wash it with anhydrous ethanol several times, and place it in an oven at 40-70°C and dry it for 6-12 hours to obtain Co-ZIF-8 metal organic precursor. Weigh 200 mg of Co-ZIF-8 metal organic precursor and 4000 mg of solid potassium chloride (KCl) and mix and grind them in a mortar, pyrolyze them at high temperature under an argon atmosphere, the pyrolysis temperature is 800-1000°C, the heating rate is 2-5°C / min, the insulation time is 1-3h, after cooling to room temperature, soak in dilute hydrochloric acid for 5-10h, centrifuge, wash with deionized water for several times until the pH is neutral, and obtain a Co-NC single atom catalyst carrier; 40 mg of the obtained Co-NC single-atom carrier material was ultrasonically dispersed in 40 mL of deionized water. Subsequently, 300 μL of ruthenium chloride aqueous solution (mass concentration of 15 mg / mL) was added dropwise to the Co-NC single-atom material dispersion (the mass ratio of metal ruthenium to transition metal-nitrogen-carbon was controlled). Ru :m CoNC =1:50), stirred for 12 hours, and then the mixed solution was freeze-dried. After freeze-drying, the obtained solid powder was placed in a porcelain boat and pyrolyzed at high temperature in a hydrogen-argon mixed atmosphere. The pyrolysis temperature was 500°C, and the temperature was kept at 500°C for 2 hours. The heating rate was 3°C / min, and the ruthenium clusters were uniformly loaded with a two-dimensional transition metal-nitrogen-carbon composite catalyst material (m Ru :m CoNC =1:50) catalyst material.

[0038] The two-dimensional transition metal-nitrogen-carbon single atom carrier prepared above uniformly supports the ruthenium cluster composite catalyst material (m Ru :m CoNC =1:50) was tested in the same way as in Example 1. The HER activity was shown in Figure 4 .

[0039] 2 mg of commercial Pt / C catalyst was weighed and dispersed in a mixed solution of 190 μL of deionized water and 300 μL of isopropanol, followed by adding 10 μL of Nafion solution (mass fraction 5%) and ultrasonically treated for 30 min to form a uniform slurry (ink); 10 μL of catalyst ink was dispersed on a glassy carbon electrode with a diameter of 5 mm. After natural drying, it was used as the working electrode, and the mercury / mercury oxide electrode and graphite carbon rod were used as the reference electrode and the counter electrode, respectively. In a standard three-electrode system, the prepared catalyst was tested for HER performance in 1M KOH solution using an electrochemical workstation (CHI660e) and a rotating disk electrode (RDE).

[0040] Test method: Electrochemical polarization curve (LSV) test was performed in the voltage range of -0.6~0.1Vvs.RHE, with a scan rate of 0.01V·s -1 , the rotation speed is 1600rpm. All potentials in LSV are corrected with ir compensation. The stability test is obtained by testing the it curve at -0.125VvsRHE.

[0041] Experimental results HER activity (see Figure 3 ) and stability (see Figure 4 ).

[0042] 2 mg of commercial Ru / C catalyst was weighed and dispersed in a mixed solution of 190 μL of deionized water and 300 μL of isopropanol, and then 10 μL of Nafion solution (mass fraction 5%) was added and ultrasonicated for 30 min to form a uniform slurry (ink); 10 μL of catalyst ink was dispersed on a glassy carbon electrode with a diameter of 5 mm. After natural drying, it was used as the working electrode, and the mercury / mercury oxide electrode and graphite carbon rod were used as the reference electrode and the counter electrode, respectively. In a standard three-electrode system, the prepared catalyst was tested for HER performance in 1M KOH solution using an electrochemical workstation (CHI660e) and a rotating disk electrode (RDE).

[0043] Test method: Electrochemical polarization curve (LSV) test was performed in the voltage range of -0.6~0.1Vvs.RHE, with a scan rate of 0.01V·s -1 , the rotation speed is 1600rpm. All potentials in LSV are corrected with ir compensation. The stability test is obtained by testing the it curve at -0.125VvsRHE.

[0044] Experimental results HER activity (see Figure 3 ) and stability (see Figure 4 ).

[0045] Preparation of ruthenium clusters uniformly loaded with two-dimensional nitrogen-carbon composite catalyst materials: Weigh 1000 mg zinc nitrate and 2000 mg 2-methylimidazole and dissolve them in 30 mL methanol. After mixing and ultrasonication, let it stand for 24 hours. Then, the obtained precipitate is centrifuged, washed with anhydrous ethanol for several times, and placed in an oven at 40-70°C and dried for 6-12 hours to obtain ZIF-8. Weigh 200 mg of ZIF-8 and 4000 mg of solid potassium chloride (KCl) and mix and grind them in a mortar, and pyrolyze them at high temperature under an argon atmosphere. The pyrolysis temperature is 800-1000°C, the heating rate is 2-5°C / min, and the insulation time is 1-3h. After cooling to room temperature, soak them in dilute hydrochloric acid for 5-10h, centrifuge them, and wash them with deionized water for several times until the pH is neutral to obtain an NC catalyst carrier. 40 mg of the obtained NC support material was weighed and ultrasonically dispersed in 40 mL of deionized water. Subsequently, 500 μL of ruthenium chloride aqueous solution (mass concentration of 15 mg / mL) was added dropwise to the Co-NC single-atom material dispersion (the mass ratio of metal ruthenium to nitrogen-carbon was controlled). Ru :m NC =1:30), stirred for 12 hours, and then the mixed solution was freeze-dried. After freeze-drying, the obtained solid powder was placed in a porcelain boat and pyrolyzed at high temperature in a hydrogen-argon mixed atmosphere. The pyrolysis temperature was 500°C, and the temperature was kept at 500°C for 2 hours. The heating rate was 3°C / min, and the ruthenium clusters were uniformly loaded with two-dimensional nitrogen-carbon composite catalyst material Ru / NC (m Ru :m NC =1:30) catalyst material.

[0046] The two-dimensional nitrogen-carbon carrier prepared above uniformly supports the ruthenium cluster composite catalyst material Ru / NC (m Ru :m NC =1:30) was tested in the same way as in Example 1. The HER activity was shown in Figure 3 .

[0047] Depend on Figure 3 The LSV results show that the two-dimensional transition metal-nitrogen-carbon single atom carrier uniformly loaded with ruthenium clusters composite catalyst material prepared in the present invention has higher alkaline HER catalytic activity than Ru / NC and commercial Pt / C and Ru / C catalysts prepared by the same method (see Figure 3 ) and stability (see Figure 4 ).

[0048] Through the comparison of different experimental examples, it is shown that the two-dimensional transition metal-nitrogen-carbon single atom carrier uniformly loaded with ruthenium cluster composite catalyst prepared by the present invention not only reduces the amount of precious metal ruthenium and reduces the cost, but also has high HER activity and stability, and shows good catalytic effect in industrial AEMWE water electrolysis devices.

[0049] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a composite cathode hydrogen evolution catalyst, characterized in that: The following steps are involved: Zinc nitrate, 2-methylimidazole, methanol and different transition metal salts were mixed and ultrasonically placed for 24 hours, and then washed with alcohol, centrifuged and dried in an oven to prepare a metal organic precursor-zeolite imidazole framework; The metal organic precursor-zeolite imidazole framework and the salt template are uniformly mixed, melted and pyrolyzed at high temperature under an inert atmosphere, and the obtained product is acid-washed, washed with deionized water, centrifuged and freeze-dried to prepare a two-dimensional transition metal-nitrogen-carbon single atom carrier material; The ruthenium source and the two-dimensional transition metal-nitrogen-carbon single atom carrier material are stirred and adsorbed in an aqueous solution, the evenly mixed solution is frozen and dried, and then subjected to high-temperature heat treatment in a hydrogen-argon mixed atmosphere to obtain a two-dimensional transition metal-nitrogen-carbon composite catalyst material uniformly loaded with ruthenium clusters.

2. The method for preparing the composite cathode hydrogen evolution catalyst according to claim 1, wherein: The transition metal salts include nitrates and acetylacetonates of iron, cobalt, nickel and copper.

3. The method for preparing the composite cathode hydrogen evolution catalyst according to claim 1, characterized in that: The mass ratio of the zinc nitrate to 2-methylimidazole is 1:(2-4).

4. The method for preparing the composite cathode hydrogen evolution catalyst according to claim 1, characterized in that: The molar ratio of the transition metal salt to zinc nitrate is (0.1-0.3):

1.

5. The method for preparing the composite cathode hydrogen evolution catalyst according to claim 1, characterized in that: The mass ratio of the metal organic precursor-zeolite imidazole framework to the salt template is 1: (10-30).

6. The method for preparing the composite cathode hydrogen evolution catalyst according to claim 1, characterized in that: Under an inert atmosphere, the pyrolysis temperature is 800-1000° C., the heating rate is 2-5° C. / min, and the time is 1-3 hours. The inert atmosphere is nitrogen or argon.

7. The method for preparing the composite cathode hydrogen evolution catalyst according to claim 1, characterized in that: The mass ratio of ruthenium to the two-dimensional transition metal-nitrogen-carbon single atom carrier material is (0.01~0.05):

1.

8. The method for preparing the composite cathode hydrogen evolution catalyst according to claim 1, characterized in that: The stirring temperature is 25-45° C., and the stirring time is 6-12 h.

9. The method for preparing the composite cathode hydrogen evolution catalyst according to claim 1, characterized in that: The high-temperature pyrolysis temperature in the hydrogen-argon mixed atmosphere is 500-700° C., the heating rate is 2-5° C. / min, and the time is 1-3 h.

10. An application of a composite cathode hydrogen evolution catalyst, characterized in that: The invention comprises a method for preparing a composite cathode hydrogen evolution catalyst as claimed in any one of claims 1 to 9, and further comprises uniformly loading the prepared ruthenium clusters with a two-dimensional transition metal-nitrogen-carbon composite catalyst as an alkaline hydrogen evolution reaction catalyst, and applying the catalyst to anion exchange membrane water electrolysis.